Hifomicetos aquáticos associados a folhas de calophyllumbrasiliense em riachos da bacia do Rio de Contas - Fiuza, Patrícia Oliveira (2017)
Freshwater hyphomycetes are the main fungal group that mediates carbon, energy and nutrient flux in freshwater ecosystems, increasing the quality of the decomposition of foliar debris. The knowledge about these fungi in Brazil is scarce, mainly regarding their ecology, diversity and distribution patterns. Aiming to expand the knowledge of aquatic hyphomycetes in Brazil and to analyze the dynamics of their communities in ChapadaDiamantinastreams,aninvestigationwascarriedoutonsubmergedleavesof C. brasiliense in three streams in the River Contas basin (Rio de Contas, Patricinho and Patricio). In October 2013 and May 2014, were carried out expeditions to Serra da Tromba, Piatã, Bahia, for the collection of green leaves of Calophyllum brasiliense, in the riparian vegetation of the Rio de Contas stream, for two decomposition experiments. Experiment 1 (E1) was carried out from November 2013 to May 2014 and experiment 2 (E2) from July 2014 to January 2015, eight months each. For both experiments, five leaves were placed in each fine mesh litter bag (30 x 30 cm, 0.5 mm mesh size) which were then submerged in three streams of the river Contas basin and tied with nylon thread trees of riparian vegetation. Every two months, six litter bags were collected from each stream (6 litter bags x 3 streams x 4 collection dates x 2 experiments, totalizing 144 bags and 720 leaves). The samples were placed in plastic bags and transported to the Laboratory of Mycology (LAMIC) of the State University of Feira de Santana in a cooler. In the expeditions, environmental variables (temperature, pH and dissolved oxygen and water velocity) and 1L of water of streams were also collected for analysis of the phosphorus and nitrogen total concentration. Leaf samples were treated according to submerged incubation and moist chamber methodologies. Fungus identification was performed at LAMIC and at the Laboratory of Microbiology of the Department of Biology at Coastal Carolina University, USA. For ecological data analysis, Simpson and evenness were used to calculate diversity; Chao 1 was used to estimate the number of taxa expected in the communities; ANOVA was performed to test for the effects of stream, experiment and collection day on fungal sporulation rate; SIMPER was used to identify the most influential taxa; ANOSIM to verify if there were differences between the communities in the streams; NMDS was used to demonstrate if there was influence of environmental variables in the communities; constancy of species was performed to evaluated the distribution of fungi on the succession; and the UPGMA was performed to visualize the similarity and groups of samples of submerged incubations and moist chambers. The chapters are divided into three sections. The first section presents two chapters with taxonomy of newrecords:(1)reviewofIngoldianfungiforBrazil,includingnewrecordsassociated with C. brasiliense, a key and illustrations for all species found in Brazil and distribution maps; and (2) are presented rare species of aquatic and facultative aquatic hyphomycetes with description, illustration and geographical distribution. In the second section were described new species of facultative aquatic hyphomycetes associatedwith C. brasiliense: (3) Selenosporella minima, (4) Synchaetomella aquatica, (5) Mirandina uncinata, and (6) Dyctiotrichocladium aquaticum; while the third and last section is an ecology chapter that analyzes the dynamics of the aquatic hyphomycetes communities associated with C. brasiliense in three streams of the Contas river basin, using submerged incubation and moist chamber methodologies. The chapter has ecological data analyzes and tables with all the taxa found in each methodology